Comparison of Point and Snow Load Deflections in Design and Analysis of Tensile Membrane Structures - Vuk S. Milošević; Biserka Lj. Marković (Advances in Civil Engineering)
Tensile membrane structures are often used as protective structures in order to provide cover from snow, rain, and direct sunlight. They are widely popular because of their advanced structural and architectural properties. Currently, their application is common at sport stadia and public spaces. There are several types of loads acting on tensile membrane structures, most importantly prestress, snow load, and wind load. However, concentrated loads also act on these structures, but they are frequently neglected during the structural analysis. There is yet no European standard on designing tensile membrane structures that would give guidance on structural analysis and incorporation of point load actions in the analysis. In addition, there is little scientific knowledge on how point loads affect tensile membrane structures. This research aims at revealing whether point loads can produce significant membrane deflections and in such way cause damage to the structure or to the objects underneath the membrane. In order to evaluate their importance, point load deflections are compared to deflections induced by snow load. This was done on a large number of numerical models differing in several parameters. Models represent typical geometries of hypar membrane structures on a square base. Obtained results show that, in many cases, point loads can produce larger membrane deflections compared to the snow load. This finding will have an impact on including the point load actions into standardization of design and analysis procedures of tensile membrane structures in Europe.